Management Accounting of Expenses for Storage of Material Resources in the Conditions of Digital Transformation of the Industrial Enterprise - I. E. Mizikovskii (Учёт. Анализ. Аудит, 2020)
The article is devoted to improving the management accounting of storage of material resources in warehouses of an industrial enterprise. Institutionalization of the information and tool space of warehouse management accounting in the context of digital transformation is one of the most urgent problems of structuring effective production management. The purpose of the research is to develop accounting and calculation methods that allow forming a high-quality information base for controlling and flexibly regulating the costs of storing material resources and finding reserves for saving them. The theoretical and methodological base of the research is structured on the basis of the application of methods of aggregation, decomposition, observation, measurement, classification, generalization, system and statistical analysis; applied approaches of two-stage distribution of indirect costs by cost centers and target costs. A comprehensive analysis of the existing model of cost allocation for storage of material resources has been conducted; new approaches to the choice of cost drivers have been proposed, as well as to the structuring their nomenclature, methods of calculation and presentation forms; the recommendations on drawing up the classifier of wasteful expenditure or dead expenses have been formed. The implementation of the proposed approaches will significantly improve the quality of the accounting and calculation process and the effectiveness of management accounting of an industrial enterprise.